2020
DOI: 10.1007/s42452-020-2563-0
|View full text |Cite
|
Sign up to set email alerts
|

Landslide susceptibility mapping using information value and logistic regression models in Goncha Siso Eneses area, northwestern Ethiopia

Abstract: Goncha Siso Eneses area of East Gojam Zone in northwestern Ethiopia is one of the most landslide-prone regions, which is characterized by frequent landslide occurrences causing fatalities and damages in cultivated and non-cultivated lands, infrastructure and properties. Hence, preparing a landslide susceptibility map is very helpful in reducing the damages in infrastructure and properties and loss of animal and human lives. In this study, GIS-based information value and logistic regression models were applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 37 publications
(47 reference statements)
1
70
0
Order By: Relevance
“…This correlation indicated that landslide probability increase as the slope gradient increases(Sun 2009), however, it may not be always true when the steep slope comprised of massive and strong slope material. Landslide may have occurred in a gentle slope when the slope material is loose and the slope subjected to modification due to anthropogenic and natural activity(Wubalem & Meten 2020). However, in the present study area, the result of the FR value indicated inTable 2, as the slope angle increased, the landslide probability is increased.…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…This correlation indicated that landslide probability increase as the slope gradient increases(Sun 2009), however, it may not be always true when the steep slope comprised of massive and strong slope material. Landslide may have occurred in a gentle slope when the slope material is loose and the slope subjected to modification due to anthropogenic and natural activity(Wubalem & Meten 2020). However, in the present study area, the result of the FR value indicated inTable 2, as the slope angle increased, the landslide probability is increased.…”
mentioning
confidence: 57%
“…It has occurred when the driving force exceeds the resistance force due to the destabilization of natural soil or rock slopes. The natural slope will be destabilized by the natural and anthropogenic factors including improper land use practice, the presence of loss sediment, heavy and prolonged rainfall, highly weathered and fractured rocks, gully and riverbank erosion, earthquake, due to superficial soil-rock interfere and unplanned urban explanation (Kifle 2013; Wubalem and Meten, 2020). The landslides activities in Ethiopia are mostly associated in northern, northwestern, central, southern, southwestern and the rift escarpments due to the presence of complex geomorphological setting, hydrological setting, geological setting, active geodynamic process and unplanned land use practice (Kifle 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations